Mortality after burn injury in children: A 33-year population-based study - Duke, J.; Rea, S.; Boyd, James; Randall, S.; Wood, F. (American Academy of Pediatrics, 2015)
OBJECTIVE: To assess the impact of burn injury sustained during childhood on long-term abstract mortality and to quantify any increased risk of death attributable to burn injury. METHODS: A population-based cohort study of children younger than 15 years hospitalized for burn injury in Western Australia (1980-2012) and a matched noninjured comparison group. Deidentified extraction of linked hospital morbidity and death records for the period 1980-2012 were provided by the Western Australian Data Linkage System. An inception cohort (1980-2012) of burn cases younger than 15 years of age when hospitalized for a first burn injury (n = 10 426) and a frequency matched noninjured comparison cohort (n = 40 818) were identified. Survival analysis was conducted by using the Kaplan-Meier method and Cox proportional hazards regression. Mortality rate ratios and attributable risk percent adjusted for sociodemographic and preexisting heath factors were generated. RESULTS: The median follow-up time for the pediatric burn cohort was 18.1 years after discharge. The adjusted all-cause mortality rate ratios for burn injury was 1.6 (95% confidence interval: 1.3-2.0); children with burn injury had a 1.6 times greater rate of mortality than those with no injury. The index burn injury was estimated to account for 38% (attributable risk percent) of all recorded deaths in the burn injury cohort during the study period. CONCLUSIONS: Burn injury sustained by children is associated with an increased risk of long-term all-cause mortality. Estimates of the total mortality burden based on in-hospital deaths alone underestimates the true burden from burn injury.